PENATAAN PEKARANGAN SEKOLAH MENJADI TEMPAT PENGOLAHAN LIMBAH UNTUK MENUNJANG KESEHATAN LINGKUNGAN (GO GREEN SCHOOL) DALAM MENINGKATKAN PROGRAM ADIWIYATA - Wahidyanti Rahayu Hastutiningtyas; Yanti Rosdiana; Fathul Qorib; Murtiyah Murtiyah (Jurnal LENTERA, 2022)
Green School is a program developed at the international level. Green School is more meaningful in shaping the attitudes of students and school residents towards the environment, which is reflected in everyday life at school. This Green School activity is related to the state of the school environment both from the standards of cleanliness, tidiness, sustainability, and the safety of the school environment, one of the things that is considered in the school environment is the sustainability that can be seen from the plants and the arrangement of the school garden. The arrangement of the school garden must be in accordance with the standards where the school garden must have more value in terms of cleanliness and safety. Purpose: to provide understanding and to organize in the school environment. Methods: Mapping productive land, conducting adiwiyata program counseling, practicing school garden planning. Result: The arrangement of the school yard into a place for waste treatment to support environmental health Go Green School is almost 80% achieved where the arrangement of the yard becomes more comfortable. the implementation before and after the arrangement of the school yard in supporting environmental health (go green school) in improving the Adiwiyata program at SDN Tulusrejo 3, Malang city, there are differences in the arrangement, where the school environment becomes more organized and looks more comfortable. In the future, the school evaluates periodically to improve the Adiwiyata program for the school environment.